A geometrically nonlinear micromorphic damage‐plasticity model. Issue 1 (18th November 2019) - Brepols, Tim; Wulfinghoff, Stephan; Reese, Stefanie
Abstract: The present article is concerned with a novel gradient‐extended 'two‐surface' damage‐plasticity model for large deformations which is based on the micromorphic approach in the sense of Forest [4]. It is discussed how the additional partial differential equation for the micromorphic (i. e., 'nonlocal') damage variable – which typically needs to be solved in case of gradient‐extended material models – can be derived in a natural way on the basis of an extended form of the principle of virtual work by assuming additional 'generalized' stresses that act within the body. As was shown recently by the authors (see [3]), the model is able to suitably counteract the well‐known mesh‐dependence problem of conventional 'local' models involving damage.